Solar Wind—Magnetosphere Coupling Functions: Pitfalls, Limitations, and Applications - Mike Lockwood (Space Weather)
Abstract Solar wind‐magnetosphere coupling functions have now been in use for almost 50 years. In that time, a very large number of formulations have been proposed. As they become increasingly subsumed into systems analysis and machine‐learning studies of the magnetosphere, it is timely to establish best practice in their derivation and study their limitations. This paper reports on a number of studies carried out to establish some key points. Particular attention is paid to the best metric used to evaluate their performance and how it depends on the application for which the coupling function is intended.